Granitoid plutons of the Brookville terrane, southern New Brunswick: petrology, age, and tectonic setting - White, Chris; Barr, Sandra; Miller, Brent; Hamilton, Michael (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT Latest Neoproterozoic and Cambrian plutons in the Brookville terrane of southern New Brunswick are termed the Golden Grove Plutonic Suite. Four groups are recognized on the basis of composition: gabbro (2 plutons), diorite - granodiorite (17 plutons), granodiorite - monzogranite (8 plutons), and syenogranite - monzogranite (7 plutons). The dioritic to granodioritic and most of the granodioritic to monzogranitic plutons form linear trends on chemical variation diagrams, suggesting that magma evolution was dominated by plagioclase and amphibole fractionation. These plutons appear to constitute a typical I-type, calc-alkaline suite characteristic of continental margin subduction zones. This interpretation is supported by U-Pb zircon ages, which show that these plutons have ages between 540 Ma and 526 Ma. A new U-Pb age of 539.6 ± 1.2 Ma from one of the gabbroic plutons shows that the gabbroic plutons are co-genetic with the dioritic to granitic plutons, although they show varied ultramafic to anorthositic and dioritic compositions as a result of crystal accumulation. The syenogranitic to monzogranitic plutons and two of the granodioritic and monzogranitic plutons, as well as felsic volcanic rocks of the Dipper Harbour volcanic unit, show chemical trends that differ from the other plutons in having A-type characteristics. A U-Pb age of 548 ± 2 Ma for the Fairville Granite, as well as similar ages for a syenogranitic pluton and the Dipper Harbour volcanic unit, suggests that these units represent early stages of magmatism in the Golden Grove Plutonic Suite.